Mesenchymal stromal cell aging impairs the self-organizing capacity of lung alveolar epithelial stem cells - Diptiman Chanda; Mohammad Rehan; Samuel R Smith; Kevin G Dsouza; Yong Wang; Karen Bernard; Deepali Kurundkar; Vinayak Memula; Kyoko Kojima; James A Mobley; Gloria A Benavides; Victor Darley-Usmar; et al. (eLife, 2021)
Multicellular organisms maintain structure and function of tissues/organs through emergent, self-organizing behavior. In this report, we demonstrate a critical role for lung mesenchymal stromal cell (L-MSC) aging in determining the capacity to form three-dimensional organoids or ‘alveolospheres’ with type 2 alveolar epithelial cells (AEC2s). In contrast to L-MSCs from aged mice, young L-MSCs support the efficient formation of alveolospheres when co-cultured with young or aged AEC2s. Aged L-MSCs demonstrated features of cellular senescence, altered bioenergetics, and a senescence-associated secretory profile (SASP). The reactive oxygen species generating enzyme, NADPH oxidase 4 (Nox4), was highly activated in aged L-MSCs and Nox4 downregulation was sufficient to, at least partially, reverse this age-related energy deficit, while restoring the self-organizing capacity of alveolospheres. Together, these data indicate a critical role for cellular bioenergetics and redox homeostasis in an organoid model of self-organization and support the concept of thermodynamic entropy in aging biology.